MALU KARENA ORANG LAIN: PERAN CITRA SOSIAL DAN KONSTRUAL DIRI RELASIONAL-INTERDEPENDEN PADA REMAJA - Oktaviani, Jovita Ikke Annisa; Budiarto, Yohanes (Esa Unggul University, 2022)
This study aims to determine the role of social image as a mediator of the relationship between relational-interdependent self-construal and vicarious embarrassment in late adolescence. The participants of this study were 127 late adolescents aged 17-22 years. Data collection was carried out by convenience sampling. Vicarious embarrassment was measured using the Vicarious Embarrassment Scale (VES) developed by Uysal et al. (2014), relational-interdependent self-construction is measured using the Relational Interdependent Self-Construal Scale (RISC Scale) (Cross et al., 2000), and social image was measured using the Consciousness of Social Face Scale (Zhang et al., 2011). The results of the study revealed that social image has a mediating effect on the role of relational-interdependent self-construal towards vicarious embarrassment, and gender does not differentiate relations between relational-interdependent self-construal vicarious embarrassment, and social image.